Euclid preparation: XLVI. The near-infrared background dipole experiment with Euclid - Kashlinsky, Alexander; Jahnke, Knud; Seidel, Gregor; Sakr, Ziad (Astronomy and astrophysics, 2024)
Verifying the fully kinematic nature of the long-known cosmic microwave background (CMB) dipole is of fundamental importance in cosmology. In the standard cosmological model with the Friedman-Lemaitre-Robertson-Walker (FLRW) metric from the inflationary expansion, the CMB dipole should be entirely kinematic. Any non-kinematic CMB dipole component would thus reflect the preinflationary structure of space-time probing the extent of the FLRW applicability. Cosmic backgrounds from galaxies after the matter-radiation decoupling should have a kinematic dipole component identical in velocity to the CMB kinematic dipole. Comparing the two can lead to isolating the CMB non-kinematic dipole. It was recently proposed that such a measurement can be done using the near-infrared cosmic infrared background (CIB) measured with the currently operating Euclid telescope, and later with Roman. The proposed method reconstructs the resolved CIB, the integrated galaxy light (IGL), from Euclid’s Wide Survey and probes its dipole with a kinematic component amplified over that of the CMB by the Compton-Getting effect. The amplification coupled with the extensive galaxy samples forming the IGL would determine the CIB dipole with an overwhelming signal-to-noise ratio, isolating its direction to sub-degree accuracy. We developed details of the method for Euclid’s Wide Survey in four bands spanning from 0.6 to 2 μm. We isolated the systematic and other uncertainties and present methodologies to minimize them, after confining the sample to the magnitude range with a negligible IGL-CIB dipole from galaxy clustering. These include the required star-galaxy separation, accounting for the extinction correction dipole using the new method developed here achieving total separation, and accounting for the Earth’s orbital motion and other systematic effects. Finally, we applied the developed methodology to the simulated Euclid galaxy catalogs, successfully testing the upcoming applications. With the techniques presented, one would indeed measure the IGL-CIB dipole from Euclid’s Wide Survey with high precision, probing the non-kinematic CMB dipole.